2019
DOI: 10.1177/0218492319836910
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary angiosarcoma: case reports and review of the literature

Abstract: Pulmonary artery angiosarcoma is a rare malignant vascular tumor with an aggressive clinical course and a poor prognosis. Hemoptysis and shortness of breath have been reported as common clinical presentations. The exact clinicopathology is unknown. A tissue specimen obtained by percutaneous fine-needle aspiration cytology or open/thoracoscopic biopsy can confirm the diagnosis based on histopathological and immunohistochemical features. The differential diagnosis includes pulmonary thromboembolism, vascular mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, some patients may be asymptomatic during the course of the disease. In this case, the patient was younger than most reported patients (Drosos et al, 2019;Virarkar et al, 2019), and showed only minor coughs with occasional hemosputum, while headache due to metastasis was prominent. These factors contributed the misdiagnosis as tuberculosis.…”
Section: Discussionmentioning
confidence: 52%
“…However, some patients may be asymptomatic during the course of the disease. In this case, the patient was younger than most reported patients (Drosos et al, 2019;Virarkar et al, 2019), and showed only minor coughs with occasional hemosputum, while headache due to metastasis was prominent. These factors contributed the misdiagnosis as tuberculosis.…”
Section: Discussionmentioning
confidence: 52%